O significado do trabalho para a pessoa com deficiência mental - Covre, Thais Kalinina Martins (2007)
The principal aim of this study was to know how a person with mental deficiency perceives both the work he does and the social relations established within the working environment. To reach such objective, it was chosen the qualitative method of research, being, the interview, the selected form of investigation. In the first part of the study, a bibliographical research was carried through and, after this stage, it was made a field research in which six formal workers with light and moderate mental deficiency were interviewed. These workers are inserted in three Brazilian companies set in the State of São Paulo, two of them, a big and a medium-sized one, located in the area of Campinas, and the third one located in the area of Vinhedo, this being a big size company. The data was collected in the place where the chosen informants work. The collected material was later analyzed and, from the speech of these workers, it was possible to assert that, in their majority, they agree on the following: they like the work they do as well as their working environment, they do not perceive anything bad in the working environment and consider their relationship with their employers and fellow workers harmonious, full or respect and fellowship. The present work shows evidence of the importance of new studies which try to find out if mental deficiency workers are really being included in the work market and if the employing companies are effectively having politics of inclusion for these workers.